Democracy and the Church-State Relationship - Kainz, Howard P. (Philosophy & theology, 1991)
There are good historical reasons for emphasis on separation of church and state in a democracy, but the separation can be carried too far. Concerning the relationship of church and state, various Chrístian denominations divide up into separatists and unificationists, and each tendency can lead into extremes which could under certain conditions be inimical to democracy. Going beyond questions of constitutional separation, one may argue for a mutual utility and complementarity of church and democratic polity. Whether a strictly necessary relationship is entailed is a more complex problem.